Hsa‐miR‐409‐3p regulates endothelial progenitor senescence via PP2A‐P38 and is a potential ageing marker in humans. Issue 5 (9th February 2023) - Lee, Yi‐Nan; Wu, Yih‐Jer; Lee, Hsin‐I; Wang, Hsueh‐Hsiao; Hung, Chung‐Lieh; Chang, Chiung‐Yin; Chou, Yen‐Hung; Tien, Ting‐Yi; Lee, Chun‐Wei; Lin, Chao‐Feng; Su, Cheng‐Huang; Yeh, Hung‐I
Abstract: We explored the roles of hsa‐microRNA (miR)‐409‐3p in senescence and signalling mechanism of human endothelial progenitor cells (EPCs). Hsa‐miR‐409‐3p was found upregulated in senescent EPCs. Overexpression of miRNA mimics in young EPCs inhibited angiogenesis. In senescent EPCs, compared to young EPCs, protein phosphatase 2A (PP2A) was downregulated, with activation of p38/JNK by phosphorylation. Young EPCs treated with siPP2A caused inhibited angiogenesis with activation of p38/JNK, similar to findings in senescent EPCs. Time series analysis showed, in young EPCs treated with hsa‐miR‐409‐3p mimics, PP2A was steadily downregulated for 72 h, while p38/JNK was activated with a peak at 48 hours. The inhibited angiogenesis of young EPCs after miRNA‐409‐3p mimics treatment was reversed by the p38 inhibitor. The effect of hsa‐miR‐409‐3p on PP2A signalling was attenuated by exogenous VEGF. Analysis of human peripheral blood mononuclear cells (PBMCs) obtained from healthy people revealed hsa‐miR‐409‐3p expression was higher in those older than 65 years, compared to those younger than 30 years, regardless of gender. In summary, hsa‐miR‐409‐3p was upregulated in senescent EPCs and acted as a negative modulator of angiogenesis via targeting protein phosphatase 2 catalytic subunit alpha (PPP2CA) gene and regulating PP2A/p38 signalling. Data from human PBMCs suggested hsa‐miR‐409‐3p a potential biomarker for human ageing.